Impacts of Cultivated Land Reclamation on the Climate and Grain Production in Northeast China in the Future 30 Years - Qingling Shi; Yingzhi Lin; Enpei Zhang; Haiming Yan; Jinyan Zhan (Advances in Meteorology)
China, as a large agricultural country as well as a major country with great demand for grain, has played a more and more important role in the international grain market. As Northeast China is one of the major commodity grain bases in China as well as one of the regions with the highest intensity of human activities, it plays an important role in influencing the global food security. This study first generally analyzed the cultivated land reclamation and the climate change of temperature and precipitation in Northeast China during 2000–2010. Then, on the basis of these data, the climatic effects of cultivated land reclamation in Northeast China during 2030–2040 were simulated by the weather research forecast (WRF) model. Finally, the possible effects of the climate change on the grain yield and the potential influence on the food security were analyzed. The simulation result indicated that the temperature in Northeast China would be increasing on the whole, while the precipitation would be decreasing. The result of this study can provide some theoretical support to the agricultural economic development in Northeast China and serve the national macropolicy and food security strategy of the whole China.